Biocompatible ultrananocrystalline diamond coatings for implantable medical devices. (15th July 2014) - Auciello, Orlando; Gurman, Pablo; Guglielmotti, Maria B.; Olmedo, Daniel G.; Berra, Alejandro; Saravia, Mario J.
Abstract: Abstract : A novel multifunctional and biocompatible ultrananocrystalline diamond (UNCD) film technology developed recently represents a new material with a unique combination of functionalities, including biocompatibility, to enable a new generation of implantable medical devices and scaffolds for tissue engineering. Following a description of the synthesis and properties of UNCD films and a comparison with other diamond film technologies, this article focuses on descriptions of key UNCD-based medical devices to treat specific medical conditions requiring effective therapies: (1) A UNCD-coated microchip (artificial retina) implantable inside the eye on the retina to restore partial vision to people blinded by retinitis pigmentosa and macular degeneration produced by genetically induced degeneration of the retina photoreceptors. (2) A UNCD-coated intraocular device for treatment of glaucoma in the eye. (3) UNCD-coated metal dental implants with potential order of magnitude longer life and superior performance than current implants.